Rapid feedback processing in human nucleus accumbens and motor thalamus. (April 2015) - Schüller, Thomas; Gruendler, Theo O.J.; Jocham, Gerhard; Klein, Tilmann A.; Timmermann, Lars; Visser-Vandewalle, Veerle; Kuhn, Jens; Ullsperger, Markus
Abstract: The nucleus accumbens (NAcc) and thalamus are integral parts in models of feedback processing. Deep brain stimulation (DBS) has been successfully employed to alleviate symptoms of psychiatric conditions including obsessive-compulsive disorder (OCD) and Tourette's syndrome (TS). Common target structures are the NAcc and the ventral anterior and ventro-lateral nuclei (VA/VL) of the thalamus, for OCD and TS, respectively. The feedback related negativity (FRN) is an event-related potential associated with feedback processing reflecting posterior medial frontal cortex (pMFC) activity. Here we report on three cases where we recorded scalp EEG and local field potentials (LFP) from externalized electrodes located in the NAcc or thalamus (VA/VL) while patients engaged in a modified time estimation task, known to engage feedback processing and elicit the FRN. Additionally, scalp EEG were recorded from 29 healthy participants (HP) engaged in the same task. The signal in all structures (pMFC, NAcc, and thalamus) was differently modulated by positive and negative feedback. LFP activity in the NAcc showed a biphasic time course after positive feedback during the FRN time interval. Negative feedback elicited a much weaker and later response. In the thalamus a monophasic modulation was recorded during the FRN time interval. Again, this modulation was more pronounced after positive performance feedback compared to negative feedback. In channels outside the target area no modulation was observed. The surface-FRN was reliably elicited on a group level in HP and showed no significant difference following negative feedback between patients and HP. German Clinical Trial Register: Neurocognitive specification of dysfunctions within basal ganglia-cortex loops and their therapeutic modulation by deep brain stimulation in patients with obsessive compulsive disorder and Tourette syndrome, http://www.drks.de/DRKS00005316 . Highlights: Concurrent EEG and LFP (NAcc and thalamus) recording during feedback processing. No difference in scalp FRN between controls and patient group. All structures differentiate between positive and negative performance feedback. Positive feedback is followed by larger LFP deflections in the NAcc and thalamus.